GAMBARAN SISTEM PENYIMPANAN OBAT DI PUSKESMAS GALESONG UTARA KECAMATAN GALESONG UTARA KABUPATEN TAKALAR - Muhammad Tahir, Muhammad Tahir; Mutiarah (Jurnal Kesehatan Yamasi Makassar, 2024)
Research has been carried out at the North Galesong Health Center, North Galesong District, Takalar Regency to find out the description of the Drug Storage System in the Health Center. This research was conducted by direct interviews and is descriptive in nature. Apt. Hj. Kartini, S. Farm. As the Person in Charge of the Pharmacy stated that the drug storage at North Galesong Health Center had met the existing storage standards starting from the drugs being arranged alphabetically for each dosage form, the drugs being stored on the floor placed on pallets, the method of storing drugs that met the requirements such as the drugs being rotated with the FEFO (First Expired First Out) and FIFO (First In First Out) systems, liquids, ointments and injectable drugs were stored in the center of the shelf, drugs that required cold temperatures were stored in the refrigerator, there were no expired drugs in the drug store, desinfe ctan is placed separately from other drugs, drugs that have the same expiration date are used which arrive first, there are no drugs that are of poor quality, drugs that have a similar appearance and name (LASA; Look Alike Sound Alike) are not placed close together, liquid drugs are separated from solid drugs